WAVELET-DCT BASED IMAGE CODER FOR VIDEO CODING APPLICATIONS - Chai, Beng Seow (Universiti Teknologi PETRONAS, 2007)
This project is about the implementation ofWavelet-DCT intra-frame coder for video coding applications. Wavelet-DCT is a novel algorithm that uses Forward Discrete Wavelet Transform (DWT) to compute DCT. It is proved that the algorithm has better compression performance for difference images compared to conventional DCT. This is possible since the algorithm allows discarding insignificant DWT coefficients or more popularly known thresholding the DWT coefficients while computing the DCT. In video coder applications, wavelet-DCT is capable to achieve greater compression. This project is a feasibility study on the performance ofWavelet-DCT in video coder applications. ASIMULINK model for conventional intra-frame coder is developed and tested, with very significant data bit reduction achieved. Then, the conventional DCT block has been replaced with a Wavelet-DCT block. In the study, on one hand, experiment is conducted on difference image for conventional intra-frame coder; on the other, the same difference image with Wavelet-DCT based intra-frame coder. The thresholding algorithm is used to remove some ofthe insignificant DWT coefficients from the difference image. The main objective is to achieve a better compression capability for difference image within video coding applications. The project's experimental results supports our claim that implementation ofWavelet-DCT in intraframe coder within a video coding application could improve the system's performance with a greater compression ratio at the same Mean Squared Error.